FIB-SEM investigation of laser-induced periodic surface structures and conical surface microstructures on D16T (AA2024-T4) alloy - Salimon, I; Mailis, S; Salimon, A; Korsunsky, A (MDPI, 2020)
The use of aluminum alloy AA2024-T4 (Russian designation D16T) in applications requiring a high strength-to-weight ratio and fatigue resistance such as aircraft fuselage often demands the control and modification of surface properties. A promising route to surface conditioning of Al alloys is laser treatment. In the present work, the formation of ripples and conical microstructures under scanning with femtosecond (fs) laser pulses was investigated. Laser treatment was performed using 250 fs pulses of a 1033 nm Yb:YAG laser. The fluence of the pulses varied from 5 to 33 J/cm2. The scanning was repeated from 1 to 5 times for different areas of the sample. Treated areas were evaluated using focused ion beam (FIB)- scanning electron microscopy (SEM) imaging and sectioning, energy-dispersive X-ray (EDX) spectroscopy, atomic force microscopy (AFM), and confocal laser profilometry. The period of laser-induced periodic surface structures (LIPSS) and the average spacing of conical microstructures were deduced from SEM images by FFT. Unevenness of the treated areas was observed that is likely to have been caused by ablation debris. The structural and elemental changes of the material inside the conical microstructures was revealed by FIB-SEM and EDX. The underlying formation mechanisms of observed structures are discussed in this paper.